The reading comprehension and writing of texts in the students of the 3rd year of secondary school - Silva de Montoya, Vilma Raquel (2022)
This research aimed at the relationship between reading comprehension and the writing of texts of the students of the educational institution "presentation of Mary" of the 3rd High School in the field of the UGEL 04-comas of Lima Metropolitano-2018, the Research was of descriptive type correlate, of application level and non-experimental design, the sample was 100 students, as technique the survey was used and as instrument the questionnaire was used. According to the results, 34.00% of the students surveyed perceive a good level in the development of the reading comprehension variable, 42.00% perceive a regular level and 24.00% perceive a bad level. Likewise, 35.00% of the students surveyed present a good level with respect to the text-writing variable, 47.00% have a regular level and 18.00% have a bad level. On the other hand, it was concluded that there is a significant relationship between the reading comprehension and the writing of texts of the students of the educational institution "presentation of Mary" of the 3rd of secondary of the field of the UGEL 04-comas of Lima Metropolitan-2018, according to the correlation of Spearman of 0675 represented this result as moderate with a statistical significance of p = 0.001 being less than the 0.01.